Pengaruh Kepentingan Nasional Dalam Pelaksanaan Politik Luar Negeri Bebas Aktif - Anita Wijayanti (Kybernology : Journal of Government Studies, 2022)
The implementation of Indonesia's foreign policy in the form of "Free and Active Politics" in its development since the founding of the Indonesian state was influenced not only by the domestic situation but also by the growth of the international political climate that occurred at that time. The rapidly changing international political climate must be followed and analyzed continuously for the sake of national interest. Furthermore, the steps to respond to these changes must be decided in the implementation of foreign policy to achieve the national interest. The use of the concept of national interest here is to explain the noble ideals that Indonesia wants to achieve with a free and active foreign policy. This paper aims to highlight the dynamics of the meaning of "free and active" in Indonesia's foreign policy in terms of domestic conditions at that time and how Indonesia's foreign policy was able to respond to international political challenges that have occurred since the early days of independence until now, which are none other than policies. It was made in the national interest in order to maintain the state of Indonesia as an independent and sovereign state in the midst of a turbulent world